Soil, treated biowaste, sludge and waste. Digestion with a hydrochloric (HCl), nitric (HNO3 ) and tetrafluoroboric (HBF4 ) or hydrofluoric (HF) acid mixture for subsequent determination of elements. (30th November 2020) - British Standards Institution,
No abstract available